2008
DOI: 10.4018/jdm.2008070102
|View full text |Cite
|
Sign up to set email alerts
|

Using Iconic Graphics in Entity-Relationship Diagrams

Abstract: This study reports on an experiment examining the impact of iconic graphics on participants' understanding of domains represented by entity relationship diagrams. Cognitive load theory and the cognitive theory of multimedia learning are used to hypothesize that iconic graphics reduce the cognitive load of model viewers, leading to more complete mental models and consequently improved understanding. Results, as measured by transfer (problem solving) tasks, confirm the main hypothesis. Additionally, iconic image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 49 publications
2
22
0
1
Order By: Relevance
“…This view is contradicted by research in diagrammatic reasoning, which shows that the form of representations has an equal, if not greater, influence on human understanding and problem solving performance as their content [42,76]. Empirical studies confirm that the visual appearance of RE notations significantly affects understanding, especially by novices [51,62].…”
Section: Previous Researchmentioning
confidence: 94%
See 2 more Smart Citations
“…This view is contradicted by research in diagrammatic reasoning, which shows that the form of representations has an equal, if not greater, influence on human understanding and problem solving performance as their content [42,76]. Empirical studies confirm that the visual appearance of RE notations significantly affects understanding, especially by novices [51,62].…”
Section: Previous Researchmentioning
confidence: 94%
“…Semantically transparent symbols reduce cognitive load because they have built-in mnemonics, making it easier to learn and remember what they mean [70]. Such representations improve speed and accuracy of understanding, especially by naïve users [7,51].…”
Section: Definition Of Principlementioning
confidence: 99%
See 1 more Smart Citation
“…Semantically direct representations reduce cognitive load: their meaning can be perceived directly or easily. This kind of representations speeds-up concepts recognition, especially for novices [4,27]. According to [5], current visual notation design practice is characterised by:…”
Section: Background and Related Researchmentioning
confidence: 99%
“…Some studies have shown that the use of additional or complementary graphical icons can assist users in processing representational information [39]. Mendling et al [40], for instance, argued that a suitable strategy for making process models more understandable is to develop iconic representations for the different activities in the process.…”
Section: Iconic Representationsmentioning
confidence: 99%